2018
DOI: 10.22270/jddt.v8i6.2049
|View full text |Cite
|
Sign up to set email alerts
|

An updated review on Anti-Alzheimer’s herbal drugs

Abstract: Alzheimer’s disease (AD) is related to cognitive impairment, dementia observed generally in aged population due to neurodegeneration in an ongoing manner. It gradually worsens memory power of the patient. The hallmark diagnosis features includes formation of senile plaques and Neurofibrillary tangles (NFT’S) [1, 2]. Too little availability of Acetyl choline (ACh) a neurotransmitter in the cerebral region due to metabolism by an enzyme Acetyl choline esterase before showing its action and neural death are the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The hallmark diagnosis of Alzheimer's disease features includes formation of senile plaques and neurofibrillary tangles (Sanka et al, 2018). Numerous hypotheses have been put forward on the basis of the various causative factors in order to explain this multifactorial disorder (Sanka et al, 2018). Some of them included are: cholinergic hypothesis, amyloid beta hypothesis, Tau hypothesis and Inflammation hypothesis (Sanka et al, 2018).…”
Section: Alzheimer's Disease: Diagnosis and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The hallmark diagnosis of Alzheimer's disease features includes formation of senile plaques and neurofibrillary tangles (Sanka et al, 2018). Numerous hypotheses have been put forward on the basis of the various causative factors in order to explain this multifactorial disorder (Sanka et al, 2018). Some of them included are: cholinergic hypothesis, amyloid beta hypothesis, Tau hypothesis and Inflammation hypothesis (Sanka et al, 2018).…”
Section: Alzheimer's Disease: Diagnosis and Treatmentmentioning
confidence: 99%
“…Numerous hypotheses have been put forward on the basis of the various causative factors in order to explain this multifactorial disorder (Sanka et al, 2018). Some of them included are: cholinergic hypothesis, amyloid beta hypothesis, Tau hypothesis and Inflammation hypothesis (Sanka et al, 2018). Various therapeutic targets to treat Alzheimer's disease are 1) Targeting amyloid beta protein (Antiamyloid approach), 2) Targeting amyloid transport, 3) Modulation of Secretase enzyme, 4) Targeting amyloid clearance, 5) Amyloid based vaccination therapy, 6) Targeting Tau protein, and 7) Neurogenesis (Sanka et al, 2018).…”
Section: Alzheimer's Disease: Diagnosis and Treatmentmentioning
confidence: 99%
“…Several Herbal Medicines have been used since ancient times for treatment of neurological disorders because of their lesser side effects and greater efficacy. Such herbs are Ashwagandha (Withania somnifera), Turmeric (Curcuma longa), Shankhpushpi (Convolvulus pluricaulis), Ginkgo Biloba, Saffron (Crocus sativus), Brahmi (Bacopa monnieri), Gotu Kola (Centella asiatica), Triphala (emblica officinalis), Cat's claw (uncaria tomentosa) [53] .…”
Section: Herbal Drugs Used In the Management Of Admentioning
confidence: 99%
“…The flavonoids and Terpens in the extract significantly inhibit acetylcholinesterase activity in brain. Ginkolides is a potent anti-oxidant with cholinergic and neuroprotective activities hence it protects against Aβ-Protein induced oxidative damage [53] . Gb is used as an initial treatment for early-stage AD and vascular dementia.…”
Section: Ginkgo Bilobamentioning
confidence: 99%
“…According to Ayurvedic literature and practices, A. calamus plant extract was prescribed for several problems related to digestion, insomnia, epilepsy, cough, fever, and neurosis. The active compounds of this plant were reportedly involved in the acetylcholinesterase degradation [ 56 ]. Studies have shown that A. calamus is an effective source of medication that can help in preventing memory impairment or increasing memory by stress reduction by controlling inflammation and reactive oxygen species [ 57 ].…”
Section: Herbal Treatment To Cure Alzheimer’s Diseasementioning
confidence: 99%